2016
DOI: 10.1590/1984-70332016v16n4a45
|View full text |Cite
|
Sign up to set email alerts
|

Selection in energy cane families

Abstract: Abstract:The objective of this study was to identify superior parents for crosses and the best families to breed new clones of energy cane. The best-performing parents were RB867515, RB93509, KRAKATAU, IM76-228, IM76-229, and US85-1008. The heritability (0.59 -0.85)and accuracy values (0.76 -0.92)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
4
8
0
Order By: Relevance
“…In studies with sugarcane families, Jackson et al (1995) and Moraes et al (2010) found similar values for these traits. In studies of energy cane families, Silveira et al (2016) found very similar values of CVe for the traits PC, FIB, TCH, TSH, and TFH to those obtained in this study. The high value of CVe for TCH, according to the classification proposed by Gomes (1990), can be attributed in part to the data heterogeneity and the strong environmental influence on this complex trait.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In studies with sugarcane families, Jackson et al (1995) and Moraes et al (2010) found similar values for these traits. In studies of energy cane families, Silveira et al (2016) found very similar values of CVe for the traits PC, FIB, TCH, TSH, and TFH to those obtained in this study. The high value of CVe for TCH, according to the classification proposed by Gomes (1990), can be attributed in part to the data heterogeneity and the strong environmental influence on this complex trait.…”
Section: Resultssupporting
confidence: 86%
“…These results are consistent with the study of Kang et al (1983) for BRIX and TCH; of Melo et al (2006), for PC, BRIX, FIB, and TCH; and in the stufy of Silva et al (2011), for the traits BRIX, PC, TCH, and TSH. Silveira et al (2016) found very close heritability values for PC, FIB, and TCH, and lower values for TSH and TFH in evaluations of sugarcane families.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…There are continuous cylinders of sclerenchyma close to the periphery. S. spontaneum contained high fiber content, where this is in harmony with other species (Silveira et al, 2016). Ground Tissue is parenchymatous without the demarcation cortex and pith.…”
Section: Saccharum Spontaneumsupporting
confidence: 72%
“…The significance of the variances of progenies (genetic) at the 1% probability level by the F test, for the four experiments, indicates the existence of genetic variability between the progenies of each type of pollination and allows for genetic gains through selection (Silveira et al, 2016). This significant effect, in particular the progenies from self-pollination, in which of the four experiments obtained greater percentage gains in three of them, may be related to the higher level of homozygosis, expressing with it greater divergence between the progenies, the one that allows the percentage of larger genetic gains (Vargas-Reeve et al, 2013).…”
Section: Continuaçãomentioning
confidence: 98%